Willingness to pay for entry to ecotourism mangrove forest - Iswarani, Ni Putu Diva; Nasir, Aqiqah Amalia; Hadi, Genta Arkana; Ditia, Syifa; Vidyanidhi, Putu Cintya (Jurnal Bisnis Kehutanan dan Lingkungan, 2025)
Background: Mangrove forests play a vital role in maintaining biodiversity, supporting ecosystem services, and protecting coastal areas from natural disasters. However, increasing human activities such as deforestation and pollution threaten their sustainability. Understanding the willingness to pay (WTP) for mangrove conservation and ecotourism is essential to quantify public perception of their value. This study focuses on assessing visitors’ perceptions, knowledge, preferences, and WTP for ecotourism at the Mekar Beach Mangrove Forest, Muara Gembong, Indonesia. Methods: The study used a survey method with purposive sampling, targeting 127 respondents who had visited the Mekar Beach Mangrove Forest. Primary data were collected through a closed-ended online questionnaire distributed via Google Forms. The study examined five variables—perception, knowledge, tourism preference, facilities, and WTP—and conducted validity and reliability testing using Pearson correlation and Cronbach’s Alpha (≥0.700 considered reliable). Findings: Most respondents agreed that mangrove forests should be preserved, as they provide tranquility, biodiversity, and economic benefits. Visitors showed strong preferences for nature-based tourism and environmentally friendly behavior. The site’s facilities were perceived positively. The majority of respondents expressed a WTP below IDR 15,000 for entrance tickets. Key aspects to improve include enhancing public perception, increasing environmental knowledge, aligning tourism offerings with visitor preferences, and improving facilities. Conclusion: Public perception and willingness to pay for the Mekar Beach Mangrove Forest reflect strong awareness of environmental conservation and appreciation for natural tourism. The relatively low WTP suggests the need for better promotion, education, and facility development to enhance perceived value and support sustainable ecotourism. Novelty/Originality of This Article: This study provides empirical insight into visitors’ WTP for mangrove forest conservation by integrating socio-psychological (perception, knowledge, preference) and economic (WTP) dimensions. It contributes to the understanding of how ecotourism valuation can support mangrove conservation strategies in Indonesia.